Bell-ringing study competence in the system of future education for teachers of music art - Lina Ilchuk (Vasyl Stefanyk Precarpathian National University, 2018)
In this article the problem of forming bell-ringing study competence was firstly discribed in system of preparation for future teachers of music. Was found that the quality of their professional education in pedagogic view of bell-ringing depends largely on the developed teaching conditions. The significant place takes performance of creative tasks, that simulate future professional and educational activities of teachers-musicians. Key words: music teacher, competence, bell-ringing art, bell-ringing pedagogics, creative tasks.